2016
DOI: 10.1103/physrevd.93.065031
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear quark operator renormalization at generalized symmetric point

Abstract: We compute Green's functions with a bilinear quark operator inserted at non-zero momentum for a generalized momentum configuration to two loops. These are required to assist lattice gauge theory measurements of the same quantity in matching to the high energy behaviour. The flavour non-singlet operators considered are the scalar, vector and tensor currents as well as the second moment of the twist-2 Wilson operator used in deep inelastic scattering for the measurement of nucleon structure functions.Comment: 19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…In Refs. [13,28], two loop calculations of certain Green functions with bilinear quark operator insertions were performed for a general momentum configuration parametrized by ω ¼ q 2 =p 2 . For example, ω ¼ 0 and 1 correspond to the exceptional and symmetric momentum configuration respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Refs. [13,28], two loop calculations of certain Green functions with bilinear quark operator insertions were performed for a general momentum configuration parametrized by ω ¼ q 2 =p 2 . For example, ω ¼ 0 and 1 correspond to the exceptional and symmetric momentum configuration respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Such a configuration is a nonexceptional one and hence should avoid infrared problems. The extension of the early lattice work on operator renormalization at an exceptional point of [29,30] was extended to the nonexceptional case in [32] at one loop and later to two loops in a variety of articles [33][34][35][36][37]. More recently in the lattice study of [38] the operator renormalization constants for all the flavor nonsinglet quark bilinear operators were measured and it was demonstrated that for massless quarks those for the nonexceptional configuration were much more reliable in the infrared limit.…”
Section: Introductionmentioning
confidence: 99%
“…where the operator O corresponds to any one of (2.1) and (2.2). We use a similar notation to [35][36][37] and follow the general approach provided there. The two independent external momenta, p and q, satisfy the condition for the symmetric subtraction point which is [43,44]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations